The identification of talent in sport - Arsic, J. (Sport Science & Practice, 2017)
National federations, sport clubs and other organizations in the field of sports industry set out as one of their primary goals the identification of young athletes who are likely to become top players. Sports clubs have an interest in maintaining the services of their most talented athletes in the long term, for the sake of stability and game quality. A sports talent involves a complex set of skills that are at the same time genetically determined, dependent on environmental conditions and are difficult to be measured with the satisfactory level of accuracy. Due to the expressed needs of the sports industry for the quality selection of gifted children for sports, but also a growing increase in the competition in the sports market, the identification of talent in sport is a significant problem of modern sports science and its specific challenge, as well. The reliable identification of future top athletes allows clubs to focus on the development of a small number of players, which represents a more effective management of their financial resources. In an attempt to produce young, talented athletes, researchers in sports have a big role in the cooperation with coaches, scouts and managers in determining the key elements for the identification and development of talents in sport.